2019
DOI: 10.3390/toxins11100601
|View full text |Cite
|
Sign up to set email alerts
|

Biological Stoichiometry Regulates Toxin Production in Microcystis aeruginosa (UTEX 2385)

Abstract: Harmful algal blooms (HABs) are increasing in magnitude, frequency, and duration globally. Even though a limited number of phytoplankton species can be toxic, they are becoming one of the greatest water quality threats to public health and ecosystems due to their intrinsic toxicity to humans and the numerous interacting factors that undermine HAB forecasting. Here, we show that the carbon:nitrogen:phosphorus (C:N:P) stoichiometry of a common toxic phytoplankton species, Microcystis, regulates toxin quotas duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…In this study, we observed chl a concentration indicating N secondary limitation in half of the experiments, but biovolume indicated N secondary limitation in only 25% of the experiments, and there was a weak correlation between chl a and biovolume. Chlorophyll is an N‐rich molecule, and the phytoplankton in our experiments increased chl a content per cell disproportionately when enriched with N, which has been shown elsewhere when N limitation was alleviated (Harke & Gobler, 2015; Krasikov, Aguirre von Wobeser, Dekker, Huisman, & Matthijs, 2012; Wagner et al., 2019). Additionally, the discrepancy could be due to photo‐acclimation as the phytoplankton altered chl a content per cell in response to the new light regime of the incubator (MacIntyre, Kana, Anning, & Geider, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we observed chl a concentration indicating N secondary limitation in half of the experiments, but biovolume indicated N secondary limitation in only 25% of the experiments, and there was a weak correlation between chl a and biovolume. Chlorophyll is an N‐rich molecule, and the phytoplankton in our experiments increased chl a content per cell disproportionately when enriched with N, which has been shown elsewhere when N limitation was alleviated (Harke & Gobler, 2015; Krasikov, Aguirre von Wobeser, Dekker, Huisman, & Matthijs, 2012; Wagner et al., 2019). Additionally, the discrepancy could be due to photo‐acclimation as the phytoplankton altered chl a content per cell in response to the new light regime of the incubator (MacIntyre, Kana, Anning, & Geider, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…Besides gas vesicles and pigments, other N‐rich traits in phytoplankton have been reported following cellular elemental stoichiometry as well. For example, the synthesis of N‐rich toxic secondary metabolites (e.g., microcystins) was shown to generally decrease upon N limitation and increase under P limitation, thus decreasing with cellular C : N ratio (Van de Waal et al 2009; Gobler et al 2016; Wagner et al 2019; Brandenburg et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the concentration of microcystins (cyanobacterial peptide toxins) in cyanobacterial cells has been proposed to relate to excess availability of nitrogen (e.g. Gobler et al, 2016;Wagner et al, 2019;Brandenburg et al, 2020), and this intuitively seems to be expected on the basis of the high N content of these molecules. However, the opposite has also been observed: experiments addressing the impact of N-limitation (and other growth conditions) on culture strains of various cyanobacteria have shown contradictory results, some of which may have methodological causes.…”
Section: For Further Discussion)mentioning
confidence: 99%